LEGAL PLURALISM AND THE RECOGNITION OF INDIGENOUS LAND RIGHTS: A COMPARATIVE STUDY OF INDONESIA, THE PHILIPPINES, AND CANADA - Achmad Jaelani; Reza Kautsar Kusumahpraja; Dede Agus; Jarkasi Anwar; Aristama Mega Jaya (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The regulation of customary land rights (hak ulayat) in Indonesia’s agrarian legal system reflects a structural tension between formal recognition and practical implementation. Although the 1945 Constitution of the Republic of Indonesia and the Basic Agrarian Law (UUPA) recognize indigenous peoples’ rights, such recognition remains conditional and administratively dependent, resulting in a subordinated legal position of indigenous communities. This study comparatively examines customary land governance in Indonesia, the Philippines, and Canada to identify divergent models of indigenous land recognition and to formulate an ideal regulatory framework for Indonesia. This research employs a normative juridical method with statutory, conceptual, and comparative approaches. It analyzes Indonesia’s agrarian framework, the Indigenous Peoples’ Rights Act (IPRA) of the Philippines, and the doctrine of Aboriginal title within Canadian jurisprudence. Findings indicate that Indonesia applies a conditional administrative recognition model, the Philippines adopts a statutory affirmative model through Certificates of Ancestral Domain Title (CADT) and Free, Prior, and Informed Consent (FPIC), while Canada develops a constitutional-judicial model grounded in historical occupation, reinforced by fiduciary duty and meaningful consultation. These differences reflect varying degrees of legal certainty and institutional protection of indigenous land rights. The study concludes that Indonesia requires reconstruction toward a constitutional-pluralist model grounded in dignified justice, operationalized through declaratory recognition, binding territorial demarcation, substantive consent requirements, independent dispute resolution mechanisms, and a strict public interest test for state intervention.